Equinos portadores de Streptococcus equi subespécie equi: prevalência, fatores de risco e caracterização de alelos seM - Libardoni, Felipe (2015)
Strangles is considered the main respiratory disease in horses. The etiologic agent is the bacterium Streptococcus equi subsp. equi (S. equi), responsible for approximately 30% of horse diseases worldwide notifications. The clinical signs of strangles are fever, nasal secretion and lymph node enlargement. The last one occurs due the incomplete phagocytosis of S. equi by defense cells because bacterial hyaluronic acid capsule and M protein (SeM). The epidemiology, the risk factors and the strangles control are poorly understood. The 5' end of the seM gene sequence has been used for isolate differentiation by characterization of the alleles. Therefore, this thesis aimed to study the prevalence of Streptococcus equi subsp. equi (S. equi) in healthy horses, the alleles frequency and the risk factors involved on equine adenitis. One thousand and ten nasal swabs were obtained from healthy horses from 341 farms. Twenty four horses were positive for S. equi, confirmed by PCR and DNA sequencing. The prevalence of S. equi per equine was 2.37%, and 20 farms were positive (5.86%). Risk factor analysis showed by confirming and quantifying statistically that: the number of agglomeration events that horses participate (RR: 1.6), the situation with food container shared (RR: 3.74) and the positive diagnosis for adenitis (RR: 3.20) are significant risk factors for Strangles. These results provide important epidemiological contribution to the equine industry and can give support for the disease control. In addition, the 5 'end of the gene seM was amplified by PCR and sequenced and allele characterized. It was found the same allele (SEM-61) in all the samples. These results support the hypothesis of natural selection of alleles apparently more suited to survive, persist and perpetuate in the population studied.